Effectiveness of video assisted teaching programme on knowledge regarding care of neonates undergoing phototherapy among BSc (nursing) 3rd year students of Vivekananda college of nursing in Lucknow Uttar Pradesh - Pandey, Pooja (International Journal of Contemporary Pediatrics, 2022)
Background: Neonatal period is the most vulnerable period of life with higher mortality and morbidity rate in human life. Jaundice is the condition in which the skin, sclera, body fluids and other tissues have a yellow discoloration which is caused by deposition of bile pigment. The aim of the study was to evaluate the effectiveness of video assisted teaching programme on knowledge regarding care of neonates undergoing phototherapy among BSc (nursing) 3rd year students of Vivekananda college of nursing in Lucknow. Methods: A pre-experimental study conducted on 50 BSc nursing 3rd year student studying in Vivekananda college of nursing. Sample was selected on the basis of non-probability purposive sampling technique. The data collection was done by conducting pre-test with structured knowledge questionnaire regarding care of neonates undergoing phototherapy than after 7 days interval post-test was conducted with same structured knowledge questionnaire. Results: Data was analyzed and interpreted by using both descriptive and inferential statistics. Distribution of BSc (N) 3rd year students according to level of knowledge showed that none of have adequate knowledge. Majority (62.00%) of students were having inadequate knowledge, 38.00% of BSc (N) 3rd year students were having moderate level of knowledge. Post-test knowledge scores shows that majority (54.00%) students had adequate level of knowledge, 46.00% students were having moderate level of knowledge whereas none of the students were having inadequate level of knowledge. Conclusions: Pre-test findings showed that there was inadequate knowledge on care of neonates undergoing phototherapy among BSc (N) 3rd year students which was improved after given video assisted teaching programme.